Implementasi Program Keluarga Harapan PKH Dalam Menanggulangi Kemiskinan Di Desa Batu Bandung Kecamatan Pino Kabupaten Bengkulu Selatan - Dwisnu, Erlian; Yolanda, Diherna (Jurnal STIA Bengkulu, 2025)
This study aims to analyze the implementation of the Family Hope Program (PKH) in poverty alleviation efforts in Batu Bandung Village, Pino District, South Bengkulu Regency. PKH is a conditional cash transfer program targeted at poor families with the goal of improving access to health, education, and social welfare services. The study employs a qualitative descriptive method using data collection techniques such as observation, interviews, and documentation. The results show that PKH implementation in Batu Bandung Village has had a positive impact on improving the welfare of beneficiary families, particularly in terms of education and health access. However, several challenges remain, including inaccurate targeting, limited inclusion in the Integrated Social Welfare Data (DTKS), and improper fund utilization. Supporting factors include the commitment of social facilitators and support from local government, while inhibiting factors involve low community understanding of the program’s objectives and weak oversight. Strengthening data accuracy, providing intensive assistance, and conducting continuous public awareness campaigns are necessary to enhance the effectiveness and equity of PKH implementation.